Atomic resolution tracking of nerve-agent simulant decomposition and host metal–organic framework response in real space - Maxwell W. Terban (Nature Portfolio, 2021)
Metal–organic frameworks have been shown to adsorb and decompose chemical warfare agents, but their mechanism of action is not completely understood. Here the authors quantitatively track the binding and decomposition product structures of nerve-agent simulant dimethyl methylphosphonate in host UiO-67 through in situ X-ray total scattering measurements, pair distribution function analysis, and density functional theory calculations.